2019
DOI: 10.1111/jam.14427
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic role of single‐celled fungi in ruminal microbial ecology and activities

Abstract: Summary In ruminants, high fermentation capacity is necessary to develop more efficient ruminant production systems. Greater level of production depends on the ability of the microbial ecosystem to convert organic matter into precursors of milk and meat. This has led to increased interest by animal nutritionists, biochemists and microbiologists in evaluating different strategies to manipulate the rumen biota to improve animal performance, production efficiency and animal health. One of such strategies is the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 112 publications
1
21
0
Order By: Relevance
“…However, Ramos et al [ 36 ] reported that the high-concentrate diet reduced the richness and diversity of the rumen microbiota. The total population of protozoa in ruminal fluid normally enhances with the high proportion of concentrate diet [ 3 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Ramos et al [ 36 ] reported that the high-concentrate diet reduced the richness and diversity of the rumen microbiota. The total population of protozoa in ruminal fluid normally enhances with the high proportion of concentrate diet [ 3 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the presence of LY in the rumen increases microbial growth, resulting in increased microbial protein transport to the duodenum. In general, yeast supplementation modifies the rumen microbiome population, resulting in improved VFA production and greater microbial protein synthesis [ 42 , 46 , 50 ]. When cows were fed S. cerevisiae at a rate of 56 g/hd/d, microbial protein synthesis increased by 9.3 percent [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Wang et al [7] found that adding LY to crop straw increased CH 4 and that the elevation of CH 4 production could result in increased fiber degradation under in vitro gas production. Elghandour et al [46] conducted an in vitro experiment and proposed that variations in CH 4 production between yeast cultures could be due to their varying protein, fat, fiber, and other material contents.…”
Section: Volatile Fatty Acid and Methane Productionmentioning
confidence: 99%
“…To develop more effective ruminant production systems, ruminants must have a high fermentation capacity. The ability of the microbial ecology to digest organic substances into milk and meat precursors is required for increased production [1]. Many feed additives, such as direct-fed microorganisms, are employed to promote livestock productivity.…”
Section: Introductionmentioning
confidence: 99%